Development of a web-based geographic information system application for regional mapping - Mahfud; Frman Jaya; Nur Azizah (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
The utilization of Geographic Information Systems (GIS) at the village level plays an important role in supporting the management of regional potential based on spatial data. However, the management of potential data in Cemara Village is still conducted using conventional methods and has not been integrated into a digital mapping system, resulting in limited access to information and suboptimal use in village development planning. This study aims to design and develop a web-based Geographic Information System application capable of presenting and managing spatial data on the potential of Cemara Village in an integrated and interactive manner. The research method employed is Research and Development (R&D) using the Sugiyono model, which consists of needs analysis, system design, implementation, and testing stages. Data collection was carried out through field observations, interviews with village officials, and questionnaires distributed to users. The system was developed using Leaflet.js as the main mapping library with OpenStreetMap as the base map, while spatial data were obtained through GPS coordinate collection using smartphones. The results indicate that the developed web-based GIS application is able to integrate attribute data and spatial data into a centralized system and present them in the form of an interactive digital map. Functional testing shows that all main features of the system operate in accordance with user requirements and facilitate the management and presentation of village potential information. This study contributes to the provision of a simple and applicable web-based GIS solution to support village potential management and data-driven village development planning.